2016
DOI: 10.1016/j.hemonc.2016.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Pre-operative chemoradiotherapy using capecitabine and cetuximab followed by definitive surgery in patients with operable rectal cancer

Abstract: Adding cetuximab to pre-operative concurrent capecitabine and radiotherapy provides modest efficacy with manageable toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…[44][45][46][47] Even in recent trials focused on wild-type KRAS rectal cancer, the response to neoadjuvant treatment was not markedly improved over response rates to 5FU/RT alone. 48,49 Thus, we also evaluated our unique patient-derived in vitro and in vivo models as experimental therapy testing platforms in order to develop future precision medicine strategies. Using our in vitro platform, we observed an increased response to cetuximab in two of four PDTOs with wild-type KRAS similar to the clinical observation that 50% of mCRC patients with wild-type KRAS do not benefit from anti-EGFR therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[44][45][46][47] Even in recent trials focused on wild-type KRAS rectal cancer, the response to neoadjuvant treatment was not markedly improved over response rates to 5FU/RT alone. 48,49 Thus, we also evaluated our unique patient-derived in vitro and in vivo models as experimental therapy testing platforms in order to develop future precision medicine strategies. Using our in vitro platform, we observed an increased response to cetuximab in two of four PDTOs with wild-type KRAS similar to the clinical observation that 50% of mCRC patients with wild-type KRAS do not benefit from anti-EGFR therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Cetuximab has shown promise in CRC cell line in vitro and in vivo models when combined with RT, although the combination of cetuximab with 5FU/RT in rectal cancer has failed to improve clinical response . Even in recent trials focused on wild‐type KRAS rectal cancer, the response to neoadjuvant treatment was not markedly improved over response rates to 5FU/RT alone . Thus, we also evaluated our unique patient‐derived in vitro and in vivo models as experimental therapy testing platforms in order to develop future precision medicine strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the combination of new therapies, such as molecular-targeted therapies, with RT has demonstrated improved outcomes for CRC [52]. These new drugs may not only enhance the antitumor effect of radiation but also increase damage to normal tissues.…”
Section: Future Prospects Of Cirtmentioning
confidence: 99%
“…Yang et al [13] investigated the efficacy and safety of a combined preoperative regimen, including volumetric modulated arc 24.1% (G3: 0% vs. 1.3%; p = 0.04) pCR, pathological complete response; DFS, disease-free survival; OS, overall survival; 3DCRT, three-dimensional conformal radiotherapy; ND, not defined; IMRT, intensity-modulated radiation therapy; GI, gastrointestinal; GU, genitourinary; CRT, chemoradiotherapy; CAPOX, capecitabine and oxaliplatin; VMAT, volumetric modulated arc therapy; NS, not significant; G, grade. therapy (VMAT) along with a simultaneous integrated boost consisting of 58.75 Gy (2.35 Gy per fraction) to mesorectum and 50 Gy (2 Gy per fraction) for other pelvic lymph node stations, with concurrent capecitabine.…”
Section: Radiotherapy Intensificationmentioning
confidence: 99%
“…Bazarbashi et al [ 24 ] studied the effect of adding weekly cetuximab to capecitabine concurrent with RT. The authors concluded that this combination was attainable with acceptable toxicity in LARC, and it was associated with better pCR compared to historical controls.…”
Section: Concurrent Chemotherapy Intensificationmentioning
confidence: 99%